The Influence of Free Time Reading Habit on the Writing Quality: Quasi-Experimental Study on Libyan Students in the English Department, Sirte University - Mohammad O Ramadan; Dunia Mansour; Rowida Mohammed (مجلة البيان العلمية, 2023)
This study aimed to find out the extent to which the students' understudy reading for pleasure affect their overall writing quality. The design employed in this study was quasi-experimental. The data was collected through compositions in the pre and post-tests. The sample consisted of 14 students who were chosen randomly from the Department of English at Sirte University and they were equally ascribed to the Control Group and Experimental Group (CG & EG henceforth). The EG was exposed to treatment for two months whereas the CG students were not exposed to any treatment. The data were analyzed manually and using SPSS software (T-Test). The descriptive and statistical results revealed that the EG overall writing quality has been improved compared to the CG. The study concludes with some pedagogical recommendation and suggestions for further research.